2017
DOI: 10.1016/j.jcmg.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Myocardial Scarring on CMR in Patients With Cardiac Sarcoidosis

Abstract: Objectives This study sought to perform a systematic review and meta-analysis to understand the prognostic value of myocardial scarring as evidenced by late gadolinium enhancement (LGE) on cardiac magnetic resonance imaging (CMR) in patients with known or suspected cardiac sarcoidosis. Background Although CMR is increasingly used for the diagnosis of cardiac sarcoidosis, the prognostic value of CMR has been less well described in this population. Methods PubMed, Cochrane CENTRAL, and meta-Register of Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(118 citation statements)
references
References 43 publications
5
103
0
3
Order By: Relevance
“…The presence of LGE is associated with an increased risk of death or significant ventricular arrhythmia even in patients with preserved LVEF and the risk of adverse outcomes is modulated by the burden of myocardial damage and the presence of RV dysfunction (53). A recent meta-analysis (54) of 11 studies evaluating the role of CMR in patients with sarcoidosis revealed that the presence of LGE had an odds ratio of 7.4 for identifying patients at risk for a composite endpoint that included all-cause mortality and ventricular arrhythmogenic events. Furthermore, the absence of LGE is associated with a low risk of major cardiovascular events even when the LVEF is severely impaired (55).…”
Section: Inflammatory Cardiomyopathiesmentioning
confidence: 99%
“…The presence of LGE is associated with an increased risk of death or significant ventricular arrhythmia even in patients with preserved LVEF and the risk of adverse outcomes is modulated by the burden of myocardial damage and the presence of RV dysfunction (53). A recent meta-analysis (54) of 11 studies evaluating the role of CMR in patients with sarcoidosis revealed that the presence of LGE had an odds ratio of 7.4 for identifying patients at risk for a composite endpoint that included all-cause mortality and ventricular arrhythmogenic events. Furthermore, the absence of LGE is associated with a low risk of major cardiovascular events even when the LVEF is severely impaired (55).…”
Section: Inflammatory Cardiomyopathiesmentioning
confidence: 99%
“…In particular, the late gadolinium enhancement (LGE) technique allows visualization of regions of myocardial injury due to cardiac sarcoidosis (7). These are most commonly observed in a noncoronary distribution and associated with an adverse prognosis (8,9). However, LGE cannot differentiate between active disease and chronic scarring.…”
mentioning
confidence: 99%
“…In addition to the diagnosis of cardiac sarcoidosis based on the presence of LGE, CMR can also predict SCD or ICD-aborted cardiac death in patients who underwent CMR on the suspicion of cardiac involvement of sarcoidosis [74,75]. Although those studies were single center studies involving a small number of patients, a recent meta-analysis showed the presence of LGE on CMR imaging is associated with increased risk of both all-cause mortality and arrhythmogenic events [76].…”
Section: Cviamentioning
confidence: 99%